Tantangan dan Solusi Manajemen Pendidikan Agama dalam Era Digital: Perspektif Sekolah Swasta - Khaerul, Khaerul (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
The digital era has brought significant changes across various aspects of life, including in the field of education. Religious education, as a pillar of moral and spiritual values, faces unique challenges in its implementation in schools, particularly in private schools that have their own distinctive managerial characteristics. This article aims to identify the challenges faced in the management of religious education in private schools and to offer strategic solutions that are relevant to technological advancements. The study employs a qualitative-descriptive approach, utilizing a literature review and interviews with several school principals and religious education teachers in private schools. The findings indicate that the primary challenges include the limited integration of technology, the lack of teacher training, and value shifts due to the influence of digital media. Proposed solutions include ICT-based training for teachers, the development of a digital-based religious curriculum, and the formation of virtual religious communities. These findings emphasize the importance of innovation and adaptation in the management of religious education in the digital era.